Biological control of sheep gastrointestinal nematode in three feeding systems in Northern China by using powder drug with nematophagous fungi - Liu, Xin-Yu; Chang, Fan-Fan; Zhao, Tian-Yu; Huang, Hai-Yan; Li, Feng-Di; Wang, Feng; Wang, Bo-Bo; Wang, Feng-Hui; Liu, Qi; Luo, Qian-Hui; Cai, Kui-Zheng; Zhong, Ren-Ma (Biocontrol science and technology, 2020)
This study aimed to evaluate the efficiency of the powdered formulation with the nematophagous fungi Duddingtonia flagrans against gastrointestinal nematodes of sheep under three feeding systems in Northern China. Each animal in the treatment group received approximately 5×10 5 spores/kg live weight at twice a week for 6 months. The control group received an equal amount of feeds without fungus. In the grazing system, two herds were selected in the Tongyu County in Northeast China. Among them, 70 sheep as the treatment group and 100 sheep as the control group. These results revealed that fungal group showed a greater reduction in eggs per gram of feces (EPG), infective larvae (L3) per kilogram in pasture and larvae per gram of feces (LPG) after administration and lower parasitic load burden in the tracer lambs compared with the control group (p<0.05). In the semi-confinement system, 20, 15, and 15 sheep from three individual farmers were selected from Zhangye City of Northwestern China; 20 sheep as the control group and the remaining sheep as the treatment group. The fungal group showed a greater reduction in EPG after 150 and 180 days and LGP from 60~180 days after administration (p<0.05). In the confinement feeding system, 40 lambs were randomly divided into the treatment and control groups. The results showed that no differences in EPG and LGP were observed in the two groups (p>0.05). In conclusion, the powder was efficient in controlling sheep gastrointestinal helminths under three feeding systems in Northern China.